Role of women in panchayati raj - Ambedkar, S. N. (S. Nagendra), 1962-; Ambedkar, Shilaja N. (Jaipur : ABD Publishers, 2006)
With special reference to India.
Includes bibliographical references (p. [269]-280) and index.
Keywords: Women -- Political activity -- India; Panchayat -- India